Antimicrobial Compounds Produced by Vaginal Lactobacillus crispatus Are Able to Strongly Inhibit Candida albicans Growth, Hyphal Formation and Regulate Virulence-related Gene Expressions - Wang, Shuai; Wang, Qiangyi; Yang, Ence; Yan, Ling; Li, Tong; Zhuang, Hui (Frontiers in Microbiology, 2017)
The female vaginal environment contains diverse microorganisms, and their interactions play significant roles in health and disease. Lactobacillus species are the predominant vaginal microorganisms in healthy women and relevant as a barrier to defense against pathogens, including Candida albicans. The yeast-to-hyphae transition is believed to be a determinant of C. albicans pathogenesis. In this study, we investigated the effects of vaginal isolates of L. crispatus (7 strains), L. gasseri (6 strains) and L. jensenii (5 strains) on growth, hyphal formation and virulence-related genes expression of C. albicans ATCC 10231. We found that the L. crispatus showed the most significant antimicrobial activities in microplate-based liquid medium assay (P < 0.05). All 7 cell-free supernatants (CFS) from L. crispatus strains reduced the growth of C. albicans by > 60%. The effects might be due to their productions of some secretory antimicrobial compounds in addition to H2O2 and organic acids. Furthermore, each of the CFS of Lactobacillus strains was found to significantly suppress the yeast-to-hyphae transition of C. albicans under hyphae-inducing conditions (RPMI 1640 medium supplemented with 10% fetal bovine serum). The hyphae inhibition rates of C. albicans treated by CFS from L. crispatus, L. gasseri and L. jensenii were 88.3 ± 3.02 %, 84.9 ± 6.0% and 81.9 ± 6.2 %, respectively. Moreover, the expression of hyphae-specific genes (ALS3, HWP1, ECE1, EAP1 and SAP5) and transcriptional regulatory genes (EFG1, TEC1 and NRG1) were analyzed using quantitative real-time PCR. The results demonstrated that L. crispatus CFS significantly down-regulated the expression of hyphae-specific genes ALS3 (0.140-fold)), HWP1 (0.075-fold) and ECE1 (0.045-fold), while up-regulated the expression of the negative transcriptional regulator gene NRG1 with 1.911-fold. The antimicrobial compounds from L. crispatus B145 against Candida growth were heat stable and protease resistance, but those against hyphal formation were partially sensitive to the same treatments. Our novel findings suggest that L. crispatus, a dominant Lactobacillus species associated with a healthy vagina, could strongly inhibit C. albicans growth and hyphal formation. L. crispatus might repress the expression of hyphae-specific genes (ALS3, HWP1 and ECE1) in a NRG1-dependent manner. Besides, L. crispatus B145 is highly worthwhile for probiotic investigation.